RANKING OF SEISMIC INTENSITY ATTENUATION LAWS AND MODELING OF SEISMIC SOURCES FOR SEISMIC HAZARD ASSESSMENT IN UZBEKISTAN - R. S. Ibragimov; T. L. Ibragimova; M. A. Mirzaev; S. H. Ashurov (Геодинамика и тектонофизика)
Quantitative assessments of seismic hazard in seismically active areas depend to a large extent on the intensity-distance attenuation laws which are used in calculations. To account for epistemic uncertainty in the nature of seismic effects, it is recommended to perform probabilistic seismic hazard analysis using several different attenuation relationships. The most effective tool for their selection is the ranking procedure which consists in attributing a weight to one or another equation depending on the degree of compliance between the equation-based seismic effects and the real experimental data available for the region under study. The article presents the results of ranking intensity attenuation laws derived for Central Asia. Ranking was carried out by LH and LLH methods. Based on the ranking results, these has been made a generalized attenuation model used subsequently in PSHA for Uzbekistan. Consideration was given to three alternative models of seismic sources: area sources, active faults, and seismogenic zones. Parameterization of the models considered involved determining seismic potential, frequency of recurrence of earthquakes of different energy levels, and the predominant type of motions in each earthquake source. Seismic zoning maps of Uzbekistan in points of the MSK-64 intensity scale have been compiled for different probabilities of occurrence of non-exceedance level earthquakes in the next 50 years.